The Organizational Culture And Its Relationship With Organizational Commitment Among The Employees In Ministry Of Youth And Sports Of Algeria - Tebbani Ali ., (sports creativity, 2025)
tudy Summary: 1/Title of the study: The Organizational culture and its relationship with organizational commitment among the employees in Ministry of Youth and Sports of Algeria 2/ General and partial questions : - Is there a relationship between the organizational culture and the organizational commitment of employees in the Ministry of Youth and Sports in Algeria? - Is there a relationship between organizational culture and responsibility towards the employer The staff of the Ministry of Youth and Sports of Algeria? - Is there a relationship between organizational culture and the desire to continue working? The staff of the Ministry of Youth and Sports of Algeria? 3/Hypotheses of the study: - There is a correlation between the organizational culture and the organizational commitment of employees in the Ministry of Youth and Sports in Algeria. - There is a correlation between organizational culture and responsibility towards the employer In the Ministry of Youth and Sports of Algeria. - There is a correlation between organizational culture and the desire to continue working In the Ministry of Youth and Sports of Algeria. 4/ General objective of the study: to discover the relationship between organizational culture and organizational commitment with staff at the Ministry of Youth and Sports in Algeria. 5/ The approach: Relational descriptive approach. 6/ The society of the study: (200) employees. 7/ The study sample: 100 employees 8/ Study Tools: Questionnaire. 9/ Field application procedures : - The researcher relied on the distribution of the questionnaire on the personal interviews with all the participants in the study in order to give them a clear idea of the purpose of this study, and this process was in the period from (01/12/2017) until (20/01/2018). 10/ The most important results: -There is a strong correlation between organizational culture and responsibility towards the employer With staff in the Ministry of Youth and Sports. - There is a moderately positive relationship between the organizational culture and the desire to continue working With staff in the Ministry of Youth and Sports